Chapter La Spagna di Claudio Magris, Claudio Magris in Spagna. Primo approccio al mondo ispanoamericano - Ladrón de Guevara, Pedro Luis (Biblioteca di Studi di Filologia Moderna, 2021)
Magris appears so often in the Spanish national press as to make it nearly impossible to be exhaustive. It is very difficult and complicated to talk about Claudio Magris' presence in Spain and the presence of Spain in his journalistic articles within a limited space. Therefore, the current essay focuses on some of his most important contributions, starting with his first interventions and relationships with the main newspapers, magazines and writers, as well as the editions of volumes in Castilian and Catalan, and the awards he has won. Magris is a fundamental point of reference for the intellectual world in Spain, where he is never perceived as a foreigner, let alone a stranger.